Eccentric overload training in patients with chronic Achilles tendinopathy: a systematic review. Issue 6 (11th October 2006) - Kingma, J J; de Knikker, R; Wittink, H M; Takken, T
Abstract : Background: Eccentric overload training seems to be a promising conservative intervention in patients with chronic Achilles tendinopathy. The efficacy of eccentric overload training on the outcome measures of pain and physical functioning are not exactly clear. Study design: Systematic review of the literature. Methods: Electronic databases were searched for randomised clinical trials concerning eccentric overload training in patients with chronic Achilles tendinopathy. The Delphi list was used to assess the methodological quality of the studies. Results: Nine clinical trials were included. Only one study had sufficient methodological quality. The included trials showed an improvement in pain after eccentric overload training. Because of the methodological shortcomings of the trials, no definite conclusion can be drawn concerning the effects of eccentric overload training in patients with chronic Achilles tendinopathy. Conclusion: The effects of eccentric exercise training in patients with chronic Achilles tendinopathy on pain are promising; however, the magnitude of the effects cannot be determined. Large, methodologically sound studies from multiple sites in which functional outcome measures are included are warranted.